Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.4039/ent1267-1
|View full text |Cite
|
Sign up to set email alerts
|

ESTABLISHMENT OF OLESICAMPE GENICULATAE QUEDNAU AND LIM (HYMENOPTERA: ICHNEUMONIDAE) TO CONTROL THE MOUNTAIN ASH SAWFLY, PRISTIPHORA GENICULATA (HARTIG) (HYMENOPTERA: TENTHREDINIDAE), IN NEWFOUNDLAND

Abstract: Mated female Olesicampe geniculatae Quednau and Lim were released in St. John’s, Newfoundland, to establish a biological control against the mountain ash sawfly, Pristiphora geniculata (Hartig). Two hundred and fifty-nine females were released during 1981–1984 in a field cage constructed over a mountain ash tree and provided with thousands of host larvae; 171 females were released outside the cage in 1984. A second open release of 368 P. geniculata cocoons, obtained as larvae from the field cage and presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The weak genetic structure we found for both parasitoid species matches the weak genetic structure recently described for the spruce budworm during the rising phase of the outbreak (Larroque et al, 2019). These results suggest that A. disperse 50-140 km per year from their release point (Quednau, 1990;Rose, 1976;West et al, 1994), which is comparable to observed dispersal distances of the spruce budworm (Boulanger et al, 2017;Greenbank et al, 1980) and the distances between subsets of the sampled outbreak areas in our study (Figure 2a). Thus, in continuous forested landscapes, insect parasitoids may contribute in many cases to spatial synchrony in outbreak patterns by means of the birdfeeder effect (Eveleigh et al, 2007;McCann & Rooney, 2009).…”
Section: Genetic Evidence Of Large-scale Population Connectivitysupporting
confidence: 90%
“…The weak genetic structure we found for both parasitoid species matches the weak genetic structure recently described for the spruce budworm during the rising phase of the outbreak (Larroque et al, 2019). These results suggest that A. disperse 50-140 km per year from their release point (Quednau, 1990;Rose, 1976;West et al, 1994), which is comparable to observed dispersal distances of the spruce budworm (Boulanger et al, 2017;Greenbank et al, 1980) and the distances between subsets of the sampled outbreak areas in our study (Figure 2a). Thus, in continuous forested landscapes, insect parasitoids may contribute in many cases to spatial synchrony in outbreak patterns by means of the birdfeeder effect (Eveleigh et al, 2007;McCann & Rooney, 2009).…”
Section: Genetic Evidence Of Large-scale Population Connectivitysupporting
confidence: 90%
“…Two egg parasitoids of European gypsy moth were released in Ontario from New Jersey during 1976 and 1980 (Griffiths and Quednau 1984). Successful introductions of Olesicampe geniculatae Quednau and Lim (Hymenoptera: Ichneumonidae) were made from Europe into Québec for control of the non-native mountain ash sawfly, Pristophora geniculata (Hartig) (Hymenoptera: Tenthredinidae) (Quednau 1990), and this agent was subsequently relocated to Newfoundland during the mid-1970s (West et al 1994(West et al , 2002a. Four species of parasitoids from Europe and Japan were introduced into British Columbia between 1969 and 1980 against the non-native larch casebearer, Coleophora laricella (Hübner) (Lepidoptera: Coleophoridae), and two of these were later relocated from Montana to British Columbia (Otvos and Quednau 1984).…”
Section: The Declining Era: 1970-2000mentioning
confidence: 99%
“…The parasitoid was released on the eastern shore of the St. Lawrence River between 1976 and 1978 and was found to have dispersed into the boreal zone by 1982 (Quednau 1984(Quednau , 1990. One of the populations of O. geniculatae from near Quebec City served as the source for releases at urban sites in Newfoundland between 1981 and 1986 (West et al 1994). Both biological control programs were successful, resulting in a decrease in defoliation by the sawfly in Quebec and Newfoundland (Quednau 1990;West et al 2002).…”
Section: Larch Casebearer Coleophora Laricella (Lepidoptera: Coleophmentioning
confidence: 99%